2005
DOI: 10.1152/ajpregu.00651.2004
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profiles in the testes of rats treated with lipopolysaccharide reveal localized suppression of inflammatory responses

Abstract: Cytokine profiles in the testes of rats treated with lipopolysaccharide reveal localized suppression of inflammatory responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
78
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 73 publications
9
78
0
Order By: Relevance
“…IL-10 can be induced by orchitis and is predominantly produced by testicular macrophages. 93 Overexpression of IL-10 in the testis significantly reduces the levels of inflammation in EAO models. 94 Therefore, multiple immunosuppressive factors are involved in the maintenance of immune homeostasis in testicular tissue.…”
Section: Immune Privilege In the Testismentioning
confidence: 99%
“…IL-10 can be induced by orchitis and is predominantly produced by testicular macrophages. 93 Overexpression of IL-10 in the testis significantly reduces the levels of inflammation in EAO models. 94 Therefore, multiple immunosuppressive factors are involved in the maintenance of immune homeostasis in testicular tissue.…”
Section: Immune Privilege In the Testismentioning
confidence: 99%
“…Both forms of IL-1 bind to the same receptor with the same range of biological actions, including the stimulation of activin A production by Sertoli cells, and are inhibited by IL-1ra (Okuma et al 2005a(Okuma et al , 2005b. Inflammation in the testis involves production of both IL-1 forms (O'Bryan et al 2005, Okuma et al 2005b. Rather than duplicating these studies using both forms of IL-1, however, IL-1b was employed as the bioactive ligand for all the studies described herein.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that administration of lipopolysaccharide (LPS), a potent inflammatory stimulus from the cell wall of gram-negative bacteria, provides a useful model for investigating this process in vivo and in vitro (Wallgren et al 1989, Hales 1992, Jonsson et al 2001, O'Bryan et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…The production of both cytokines by the Sertoli cells is stimulated by the developing germ cells and residual bodies (Gérard et al 1992, Jonsson et al 1999, and both cytokines have been implicated in the control of spermatogonial and spermatocyte development , Hakovirta et al 1995. Expression of IL-1 in the normal testis is relatively low, but this cytokine is up-regulated during inflammation due to production by testicular macrophages and Leydig cells (Gow et al 2001, Jonsson et al 2001, O'Bryan et al 2005. Testicular production of IL-6 also increases during inflammation in adult rats (O'Bryan et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation